Experiences of Emotional Burnout among College Students as Organizational Activists and Part-Time Workers: A Phenomenological Case Study in College Students (Literasi Nusantara, 2025)
Students who hold dual roles as organizational activists and part-time workers face increasing academic, social, and emotional demands. This study aims to explore how students at Universitas Trunojoyo Madura experience and interpret emotional exhaustion. A qualitative approach with a phenomenological method was employed to capture students’ lived experiences. Data were collected through in-depth interviews and reflective accounts of daily activities. The findings reveal that emotional exhaustion is characterized by persistent fatigue, internal pressure, difficulty in managing priorities, and withdrawal from social interactions when academic, work, and organizational responsibilities overlap. Despite these challenges, students develop coping strategies, including flexible time management, utilizing limited free time to complete tasks, and seeking emotional support from family members, partners, and peers. Furthermore, the experience of managing multiple roles contributes not only to psychological strain but also to the development of self-identity, independence, and awareness of mental health. This study suggests that higher education institutions should provide more empathetic academic policies and psychological support systems to help students balance multiple roles without compromising their emotional well-being.